The effect of chain length in terminal groups on the mesomorphic behavior of novel (−)-menthol-based chiral liquid crystal compounds with a blue phase. (20th April 2017) - Luo, Cong-Cong; Jia, Ying-Gang; Sun, Bing-Feng; Meng, Fan-Bao
Abstract : In this study, two series of novel chiral liquid crystal compounds derived from (−)-menthol with different lengths of alkyl or alkoxy as terminal groups were successfully synthesized. Abstract : In this study, two series of novel chiral liquid crystal compounds derived from (−)-menthol with different lengths of alkyl or alkoxy as terminal groups were successfully synthesized. Their chemical structure and liquid crystal properties were investigated by various experimental techniques. SeriesI, except for compoundIf, exhibits monotropic properties and the whole seriesII shows enantiotropic mesogenic properties. Both seriesI and seriesII display a platelet texture of a BP and a focal conic texture of an N* phase upon cooling. In addition, seriesII displays an iridescent oily streak texture along with selective reflection upon heating. The selective reflection wavelengths of seriesII shift to a shorter wavelength region with increasing temperature in the N* phase. For both seriesI and seriesII, a pronounced odd–even effect on the clearing temperature is observed when the parity of the terminal chain is varied. SeriesI with an odd number of terminal chains and seriesII with an even number have better order.